Potent neutralization of anthrax edema toxin by a humanized monoclonal antibody that competes with calmodulin for edema factor binding - Chen, Zhaochun (National Academy of Sciences, 2009)
This study describes the isolation and characterization of a neutralizing monoclonal antibody (mAb) against anthrax edema factor, EF13D. EF13D neutralized edema toxin (ET)-mediated cyclic AMP (cAMP) responses in cells and protected mice from both ET-induced footpad edema and systemic ET-mediated lethality. The antibody epitope was mapped to domain IV of EF. The mAb was able to compete with calmodulin (CaM) for EF binding and displaced CaM from EF-CaM complexes. EF-mAb binding affinity (0.05–0.12 nM) was 50- to 130-fold higher than that reported for EF-CaM. This anti-EF neutralizing mAb could potentially be used alone or with an anti-PA mAb in the emergency prophylaxis and treatment of anthrax infection.